The Role of EVA in Enhancing Corporate Value and Sustainability: a Case Study Approach - Marianus Hendrilensio Sanga (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
Applied financial position of corporates and calculate their actual economic profit take into account the Economic Value Added (EVA) methodology. The objective of this paper is to apply the EVA methodology to real-world corporate data, presenting a comprehensive case study that illustrates the creation of corporate value. This study is grounded in extensive literature review, including research publications and studies related to sustainability, corporate social responsibility, the sustainable value concept, and the EVA methodology itself. Additionally, the analysis draws on the corporation's financial statements, including accompanying notes, to ensure a thorough examination. Various analytical methods were employed throughout the study, including analysis, comparison, selection, abstraction, induction, deduction, determination, and statistical techniques. These methods were crucial in accurately interpreting the data and deriving meaningful insights regarding the corporation's economic performance. While the EVA methodology offers significant advantages in evaluating a corporation's value by focusing on economic profit and cost of capital, it is also subject to certain limitations and challenges. These include potential difficulties in obtaining accurate cost of capital estimates and the complexity of adjusting accounting figures to reflect true economic realities. Despite these challenges, EVA remains a powerful tool for understanding and enhancing corporate value creation.